Investigation of fluid flow pattern in a 3D meandering tube - Ibrahim, Syed; Khan Marwat, Dil Nawaz; Ullah, Naeem; Nisar, Kottakkaran Sooppy (Frontiers in Materials, 2023)
Several types of meandering channels and their mathematical simulation have been proposed and discussed widely in the open literature. In the present study, the impact of a novel meandering tube geometry on streamwise vortices and pressure losses have been determined. Using a simplified Poiseuille flow simulation approach with a sinusoidal wavy meandering tube of non-uniform radius, the onset flow separation, vertex formation, and the impact of Reynolds number on field variables and stream function has been analyzed. Moreover, the linear stability theory has been implemented to trace the vertex formation. A decrease in wavelength leads to flow separation near the tube’s surface, but the flow becomes rectilinear with a sudden disturbance caused by the meander, becoming independent of vertex generating centrifugal forces. Novel insights are provided on the impact of meandering tube geometry on fluid flow and potential applications for enhancing flow conditions are suggested.